E-MODULE OF ETHNOMATHEMATICS INNOVATION OF SALEM BREBES TYPICAL BATIK SUPPORTS UNDERSTANDING OF CONCEPTS - Nur Afni Maeliya; Eka Farida Fasha (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The lack of students' understanding of mathematics concept understandingiscaused by the use of monotonous teaching materials such as student worksheets(LKS) which are not contextual and have not been integrated with culture andthelack of technology utilization in learning. This research aims to developaninnovative ethnomathematics-based e-module by integrating SalemBrebes batikmotifs into mathematics learning to support students' concept understanding. Thisresearch is a type of research and development (R&D) with the development model used is 4D (Define, Design, Develop, Disseminate). The researchinstruments used in this study include validation sheets by media and material experts, as well as practicality questionnaires by students. The final product developed is an interactive e-module called Etnomedia which contains materialssuch as lines and angles, triangles and quadrilaterals, congruence, rows andseries, geometric transformations, and dimension three. The results of mediavalidation amounted to 90.5%, while the media validation results amountedto90.5%, while the material expert validation was 96.6%, both of which were inthevery valid category. The practicality test by students obtained a score of 86%, which is included in the very practical category. Thus, Etnomedia is consideredfeasible in the contextual learning process of mathematics andisable to foster appreciation for local culture.